Application Of ICT In Relation To Their Academic Achievement Of College Students (Journal of Namibian Studies : History Politics Culture, 2023)
The main objective of present paper is to find the relationship between the application of ICT and Academic achievement. For that 468 College students from Andaman & Nicobar Islands were selected by Stratified random sampling technique. Application of ICT scale which constructed by the investigators is used and the results were analysed and also found out that application of ICT and academic achievement have positive relationship and conclude this result will lead to holistic development in the vast country like India.